A Facile and Effective Method for Patching Sulfur Vacancies of WS2 via Nitrogen Plasma Treatment. Issue 36 (18th June 2019) - Jiang, Jianfeng; Zhang, Qinghua; Wang, Aizhu; Zhang, Yu; Meng, Fanqi; Zhang, Congcong; Feng, Xianjin; Feng, Yuanping; Gu, Lin; Liu, Hong; Han, Lin
Abstract: Although transition metal dichalcogenides (TMDs) are attractive for the next‐generation nanoelectronic era due to their unique optoelectronic and electronic properties, carrier scattering during the transmission of electronic devices, and the distinct contact barrier between the metal and the semiconductors, which is caused by inevitable defects in TMDs, remain formidable challenges. To address these issues, a facile, effective, and universal patching defect approach that uses a nitrogen plasma doping protocol is developed, via which the intrinsic vacancies are repaired effectively. To reveal sulfur vacancies and the nature of the nitrogen doping effects, a high‐resolution spherical aberration corrected scanning transmission electron microscopy is used, which confirms the N atoms doping in sulfur vacancies. In this study, a typical TMD material, namely tungsten disulfide, is employed to fabricate field‐effect transistors (FETs) as a preliminary paradigm to demonstrate the patching defects method. This doping method endows FETs with high electrical performance and excellent contact interface properties. As a result, an electron mobility of up to 184.2 cm 2 V −1 s −1 and a threshold voltage of as low as 3.8 V are realized. This study provides a valuable approach to improve the performance of electronic devices that are based on TMDs in practical electronic applications. Abstract : There are formidable challenges to essentially improve carrier scattering during the transmission of devices and distinct contact barrier between metal and semiconductors, which are caused by inevitable vacancies in transition metal dichalcogenides. To address these issues, a facile and effective defect patching approach is developed via nitrogen plasma doping, and the effective vacancies patching events are confirmed by a high‐resolution spherical aberration correction transmission electron microscopy.